1997
DOI: 10.1038/bjc.1997.220
|View full text |Cite
|
Sign up to set email alerts
|

Neoangiogenesis and p53 protein in lung cancer: their prognostic role and their relation with vascular endothelial growth factor (VEGF) expression

Abstract: Summary Following up-regulation of an angiogenesis inhibitor by the wild-type p53 protein proven recently, we have analysed on the one hand the prognostic impact of microvessel count (MC) and p53 protein overexpression in non-small-cell lung carcinoma (NSCLC) progression and, on the other hand, the inter-relation between the microvascular pattern and the p53 protein expression. Moreover, we assessed the expression of vascular endothelial growth factor (VEGF), one of the pivotal mediators of tumour angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
3
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 23 publications
8
74
3
6
Order By: Relevance
“…Again, p53 expression was not associated with TP expression. The interesting recent observation (Fontanini et al, 1997) that p53 nuclear expression correlates with angiogenesis and survival is not in accordance with our previously published results. The method of this paper considered microvessel counting in one focus of high (factor VIII assessed) vascularization while the mean score of p53-positive cells was assessed in five fields.…”
Section: Sircontrasting
confidence: 62%
See 1 more Smart Citation
“…Again, p53 expression was not associated with TP expression. The interesting recent observation (Fontanini et al, 1997) that p53 nuclear expression correlates with angiogenesis and survival is not in accordance with our previously published results. The method of this paper considered microvessel counting in one focus of high (factor VIII assessed) vascularization while the mean score of p53-positive cells was assessed in five fields.…”
Section: Sircontrasting
confidence: 62%
“…l) 1995;Kwa et al, 1996;Nishio et al, 1996) and others that find an association between p53 alterations and a favourable behaviour. However, several other studies, which evaluated both p53 mutations and p53 nuclear overexpression, have underlined a strong statistical association between p53 alterations and poor prognosis in this type of cancer (Quinlan et al, 1992;Horio et al, 1993;Mitsudomi et al, 1993;Fontanini et al, 1995a;Harpole et al, 1995;Dalquen et al, 1996;Irie et al, 1996; Dosaka-Akita et al, 1997; Fontanini et al, 1997, Fukuyama et al, 1997, stimulating further investigation in this field. As regards the discrepancies that arise between these studies, we have identified some possible causes:…”
Section: Sirmentioning
confidence: 97%
“…Seven of the articles Fontanini et al, 1996Fontanini et al, , 1997bFontanini et al, , 1998aHarpole et al, 1996;Takanami et al, 1999;D'Amico et al, 2000) were excluded because identical cohorts of patients were included in other selected publications.…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%
“…Methods: Using enzyme-linked immunosorbent assay, the levels of VEGF were determined in serum from 41 patients with untreated NSCLC (Stage: IIB,3; IIIA,6; IIIB,17; IV,15; Histology: squamous cell carcinoma,18; adenocarcinoma. 14; undetermined,9). Results: The median VEGF level was 312 pg/ml, ranging from 70 to 1440 pg/ml.…”
Section: Introductionmentioning
confidence: 99%
“…It is a soluble dimeric 34-46 kDa protein which has been implicated in endothelial cell proliferation and migration, increased vascular permeability, and stromal degradation through the activation of proteolytic enzymes [2,[4][5][6]. VEGF expression has been demonstrated in a large variety of human malignancies including breast, lung, colorectal, bladder, and ovarian cancer [2,[6][7][8][9][10][11][12][13][14][15][16]. In non-small cell lung cancer (NSCLC), expression of VEGF has been reported in 50-95% of cases [8-10,12,14 -16].…”
Section: Introductionmentioning
confidence: 99%